Tot aanval en verdediging : eene voordracht van Willem Liebknecht lid van den Duitschen Rijksdag. - Liebknecht, Wilhelm; Van Beveren, Edmond (Gent : Van Gyseghem, 1886)
Bibliotheek Anseele
Nederlands
Monografie